Variación en la realización de secuencias vocálicas en el español de la Ciudad de México bajo la Teoría de la Optimidad - López Villaseñor, Carlos Alfredo (El Colegio de México, A.C., 2023)
In the present article, I discuss linguistic and extralinguistic factors that condition the gliding of hiatus in Mexican Spanish under the Optimality Theory. Several hypotheses have been proposed on the gliding from hiatus to diphthongs: (i) phonetic (Chitorán & Hualde 2007); (ii) structural (Martínez-Pa-ricio 2010; 2010b; 2013); (iii) functional (=frequency) (López Escobedo 2004); and (iv) social (Vuskovich 2006). Throughout this article it is argued that the most important factor is (ii), considering that an alteration in the phonological constraint ranking is responsible for internal variation captured by the cophonology theory (Inkelas et al. 1997; Inkelas & Zoll 2007; Inkelas 2014: Chapter 2) that states that a language can have multiple grammars. This paper aims to provide an explanation of the recategorization phenomena (Ohala 1993; Hualde 2011; Company 2014) from hiatus to diphthongs for this dialect.